2002
DOI: 10.1093/nar/gnf071
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison of differences in the integration sites of interspersed repeats between closely related genomes

Abstract: A technique for genome-wide detection of differences in the integration site positions of interspersed repeats in related genomes (DiffIR) is described. The technique is based on a whole- genome selective PCR amplification of the repeats' flanking regions followed by a differential hybridization screening of the arrayed library of the selected amplicons. The technique was successfully applied to the comparison of the integration sites in the human and chimpanzee genomes, allowing us to discover 11 new human-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Data on insertion polymorphisms of the HS family members in the human and chimpanzee genomes were partly previously reported by us and other authors (2,6,9,11,32,35) and partly obtained using the UCSC genome browser (http://genome.ucsc.edu/cgi-bin/hgGateway, track "chimp").…”
Section: Methodsmentioning
confidence: 99%
“…Data on insertion polymorphisms of the HS family members in the human and chimpanzee genomes were partly previously reported by us and other authors (2,6,9,11,32,35) and partly obtained using the UCSC genome browser (http://genome.ucsc.edu/cgi-bin/hgGateway, track "chimp").…”
Section: Methodsmentioning
confidence: 99%
“…A fraction of endogenous JSRV flanking 5 0 -LTR sequence was amplified using the selective PCR suppression technique (Siebert et al, 1995;Lebedev et al, 2000;Mamedov et al, 2002). This technique has four main steps: (1) targeted sequences cleaved by a restriction enzyme, (2) ligation of restricted sites with an adapter pair of complementary oligonucleotides of unequal length, (3) amplification of the adapter-containing restricted fragments, and (4) preparation of libraries of amplicons.…”
Section: Evolutionary Dynamics Of Enjsrvsmentioning
confidence: 99%
“…A and T primers (Mamedov et al, 2002; Table 2) were used in the PCR suppression technique. LTR primer (designed and named LTRR by Chessa et al (2009) Inverse PCR.…”
Section: Evolutionary Dynamics Of Enjsrvsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, progress in human genome sequencing and methods of comparative genomics resulted in the identification of a new type of MGMs based on retroelement (RE) insertion polymorphism. [11][12][13][14][15] Recent studies revealed the existence of several thousands of polymorphic RE insertions in the human genome. This type of MGMs has several peculiarities making them attractive for human genetic identification purposes: (i) RE insertions are stable, that is there is no specific mechanism for withdrawing or removing an element from its insertion point; (ii) the probability of independent RE insertion in the same genomic locus is negligibly small, and the presence of RE indicates identity by descent; and (iii) simple identification.…”
Section: Introductionmentioning
confidence: 99%